Cascaded LMS Filter Based Control for SPV-SyRGWind Based Grid-Interactive Microgrid - Modi, Gaurav; Singh, Bhim (2022 IEEE 2nd International Conference on Sustainable Energy and Future Electric Transportation (SeFeT), 2022)
Performance indices of the grid-interactive microgrid fall off and defy the set IEEE std. 1547, when the load connected at its point of common coupling, starts to draw unbalanced/distorted currents. In this context, this work introduces a cascaded least mean square (C-LMS) filter-based harmonics extraction and compensator method to improve the solar photovoltaic (SPV) and wind-energy-based microgrid response. In the considered microgrid configuration, the SPV array and wind turbine are coupled to the local grid through their separate power converters, i.e., voltage source converter (VSC), and back-to-back VSC, respectively. The presented C-LMS filter is used as a prefilter to segregate the harmonics components from the load currents, and they are applied to control the grid-side power converters of the SPV array and wind turbine. The introduced C-LMS algorithm provides better attenuation to the harmonics components than the LMS method. Further, its settling time is less than the cascaded second-order generalized integrator (C-SOGI) method. Additionally, in this work, the grid side power converters of the SPV array and wind energy are efficiently utilized to provide compensation to the harmonics currents. Simulated results are presented to evident the designed algorithm's performance.